The Impact of IT Investment on Firm Performance in Bangladesh: A Resource-based Perspective - Mizanur Rahman, Mohammad; Ferdaous, Jannatul (Ushus Journal of Business Management, 2021)
Using the RBV as a theoretical backdrop, the study is intended to begin the line of inquiry: Do IT asset matter and improve the firm performance? This inductive research used panel data estimation technique for unbalanced panel data to measure, describe, and analyze the firm performance. The results reveal a mixed behavioral effect of IT asset on firm performance. The positive influence of IT asset on firm performance suggests that a firm should invest to develop IT infrastructure in order to effectively promote firm IT capability and performance. However, the inverse relationship between IT asset and firm performance suggests that IT intensive stocks are not performing well in the stock market of Bangladesh. The study explains the IT asset’s contribution to firm performance from RBV perspective in the context of Bangladesh as well as extends the literature in this field.